Strategi Corporate Social Responsibility Pamella Satu Supermarket Yogyakarta Dalam Membangun Brand Loyalty - Fatimah, Wahyu Nur; Rusdiana, Joni; Pratiwi, Rhesa Zuhriya Briyan; Mahardika, Mei Candra (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The more retail businesses in Yogyakarta, the higher the level of competition to attract consumers. This is also felt by Pamella Supermarket, which is one of the retail businesses in Yogyakarta. This research was conducted to find out how Pamella Supermarket's strategy in building brand loyalty. The retail industry is the most competitive industry, this research can help retail companies to develop more effective strategies in winning the competition. The CSR program conducted by Pamella uses the concept of triple bottom line (people, planet, profit). The existence of CSR activities can be considered by the public as a form of concern from the company so that it will increase public trust and increase brand loyalty. This research uses descriptive qualitative method with data collection using interview, observation, and documentation techniques. Data validity techniques using triangulation. The data analysis technique goes through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that Pamella has a CSR program named Pamella Peduli and has 6 activities that are the focus of its implementation, namely educational assistance, infrastructure, environment, health, humanitarian donations, and community donations. The implementation also involves employees and stakeholders. CSR activities are one of the considerations of consumers, the more companies contribute to social activities, the more loyal customers are to a brand.